2024
DOI: 10.1101/2024.05.26.24307960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lifestyle patterns in the Peruvian population: analysis of tobacco, alcohol and fruit/vegetable consumption based on a nine-year national survey

Víctor Juan Vera-Ponce,
Fiorella E. Zuzunaga-Montoya,
Luisa Erika Milagros Vásquez-Romero
et al.

Abstract: Introduction: A population's lifestyle is a factor in public health and general well-being; thus, three indicators are alcohol consumption, smoking activity, and a healthy diet. Objectives: The study aimed to determine the trends and factors associated with alcohol consumption, smoking activity, and fruit and vegetable consumption. Methods: This cross-sectional study was based on the National Survey of Demography and Family Health (ENDES) database between 2014 and 2022. Smoking status was categorized as never … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…However, according to the Demographic and Family Health Survey (ENDES) results, we observe mixed signals when focusing specifically on the Peruvian population. The survey indicated that the percentage of smokers decreased, averaging just over 6% in 2020, before slightly increasing to nearly 7% (3) .…”
Section: Introductionmentioning
confidence: 99%
“…However, according to the Demographic and Family Health Survey (ENDES) results, we observe mixed signals when focusing specifically on the Peruvian population. The survey indicated that the percentage of smokers decreased, averaging just over 6% in 2020, before slightly increasing to nearly 7% (3) .…”
Section: Introductionmentioning
confidence: 99%